2018
DOI: 10.1002/adhm.201800490
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Tissue Engineering: Tuning the Immune and Inflammatory Response to Implantable Biomaterials

Abstract: Regenerative medicine technologies rely heavily on the use of well-designed biomaterials for therapeutic applications. The success of implantable biomaterials hinges upon the ability of the chosen biomaterial to negotiate with the biological barriers in vivo. The most significant of these barriers is the immune system, which is composed of a highly coordinated organization of cells that induce an inflammatory response to the implanted biomaterial. Biomimetic platforms have emerged as novel strategies that aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 160 publications
0
67
0
Order By: Relevance
“…Given the role of the ECM in structural support of tissues, there has been significant effort in developing ECM‐based scaffolds for tissue engineering and regenerative medicine . For these applications, a biomaterial scaffold is often used to encourage the adhesion and infiltration of cells, and their differentiation and organization into functional tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the role of the ECM in structural support of tissues, there has been significant effort in developing ECM‐based scaffolds for tissue engineering and regenerative medicine . For these applications, a biomaterial scaffold is often used to encourage the adhesion and infiltration of cells, and their differentiation and organization into functional tissues.…”
Section: Introductionmentioning
confidence: 99%
“…These engineered tissues are designed with the ultimate goal of replacing damaged or diseased tissue. However, as with all materials implanted into the body, the immune response significantly influences the ability of engineered tissues to integrate and functionally interact with the host . The initial inflammatory response to implantation is dominated by activation of innate immune cells, including neutrophils and macrophages, followed by the later arrival of dendritic cells (DCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruited monocytes are then differentiated into macrophages in the presence of various proinflammatory cytokines produced by the other immune cells. These macrophages then adhere on the implanted materials, and the physicochemical properties of the materials play significant roles in macrophage plasticity, which influence the tissue healing process . It has been reported that the immune response to biomaterials may be attributed to the interactions between various proteins and the implanted biomaterials.…”
Section: Immune Responses and Immunomodulation By Biomaterialsmentioning
confidence: 99%
“…Tissue engineering aims to fabricate biomimetic living tissues in vitro and in vivo and various biomaterials have been developed by tissue engineering technologies (Taraballi et al, ; Vedadghavami et al, ). Likewise, a number of cell‐based bone grafting materials have been developed using animal‐derived components (e.g., type I collagen) (Irawan, Sung, Higuchi, & Ikoma, ), biodegradable synthetic polymers (e.g., polylactic acid) (Gutierrez‐Sanchez, Escobar‐Barrios, Pozos‐Guillen, & Escobar‐Garcia, ), and ceramic materials (e.g., hydroxyapatite) (Przekora, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%